Decentralised network architecture for cloud manufacturing. Issue 4 (4th May 2017) - Škulj, Gašper; Vrabič, Rok; Butala, Peter; Sluga, Alojzij
Abstract : In the context of advanced manufacturing, new models inspired by Internet technologies are being developed. The cloud manufacturing model strives to offer a similar experience for seekers of manufacturing services as cloud computing does for the users of the web: manufacturing clouds intend to offer manufacturing resources as services, much like processing power and storage space are available as services in cloud computing. The resulting business situation is favourable for both the service providers and the service end-users, especially in a highly dynamic manufacturing environment. Existing cloud manufacturing models operate in a centralised way through a cloud manufacturing platform, the management of which is identified as a critical part of the manufacturing cloud operation. In the article, a decentralised network architecture for cloud manufacturing is proposed. The architecture builds upon the concept of autonomous work systems for use as service providers. The operation of the system based on the architecture is described, wherein special attention is given to the communication within the emerged networks of service providers. Technical feasibility of the approach is also demonstrated. It is expected that the decentralised approach will enable a more flexible and scalable manufacturing cloud, which will have the ability to actively co-evolve with its environment.